Evaluation of the Implementation of Merdeka Curriculum as an Effort in Overcoming Bullying at SMPN 1 Sungai Selan - Indar Cahyani, Laila; Heryahya, Andang (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
The independent curriculum is a curriculum concept that aims to provide more optimal learning for students. In this curriculum, intracurricular learning is carried out with a variety of methods so that students can have strong concepts and strengthen their competencies. This study aims to evaluate the implementation of the independent curriculum in overcoming bullying at SMPN 1 Sungaiselan. This type of research is descriptive qualitative using the CIPP model (Context, Input, Process and Product). The results of this study are: Context Evaluation, The principal and teachers of SMPN 1 Sungaiselan have received sufficient briefings related to the independent curriculum. Input Evaluation, There are obstacles in the classroom learning process such as the uneven distribution of infocus media, projectors that support the learning process. And there has been no special training on the independent teaching platform which focuses on differentiated learning. Process Evaluation, Based on the Decree of the Minister of Education and Culture number 262 / M / 2022 the junior high school curriculum structure is divided into two main learning activities, namely Intracurricular learning and Project learning to strengthen the Pncasila Student Profile (P5). Learner-centered intraculiker learning at SMPN 1 Sungaiselan refers to teaching modules and Atp as a learning reference. Product Evaluation, The results of the implementation of the independent curriculum in overcoming bullying at SMPN 1 Sungaiselan can be seen from the percentage of students' understanding of physical, verbal, and cyberbullying. In this case, 77.9% of SMPN 1 Sungaiselan students really know or understand physical bullying. And 73.7% of SMPN 1 Sungaiselan students have never committed acts of physical violence or physical bullying. And 88.4% of SMPN 1 Sungaiselan students understand and know the forms of verbal bullying. And 64.2% of SMPN 1 Sungaiselan students have never committed acts of verbal bullying, finally the understanding of cyberbullying in SMPN 1 Sungaiselan students has increased by 90.5% and 84.2% of students have never committed acts of cyberbullying at school. The percentage results show that the understanding of physical bullying, verbal bullying, and cyberbullying and student actions are directly proportional